Ir Q J Breast Dis 2018
DOI: 10.30699/acadpub.ijbd..11.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compassion-Focused Therapy on Body Image and Marital Satisfaction in Women with Breast Cancer

Abstract: Introduction: Breast cancer is one of the most common cancers among women. The purpose of this study was to investigate the effectiveness of compassion focused therapy on body image and marital satisfaction in women with breast cancer. Methods : This research utilized a pre-test and post-test semi-experimental design with a control group. A total of 30 subjects were selected from women with breast cancer presenting to Imam Khomeini Hospital in Tehran in 2017. They were then randomly assigned to experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…The results showed that the use of compassionfocused therapy has significantly reduced the components of marital conflict. Results of this finding with the findings of Neff and Barat Wass (2013); Khalatbari, Hemmati Sabet and Mohammadi (2018); Rajabi et al (2017) are consistent. Explaining this finding, we can say that people with compassion are able to resolve their interpersonal differences by considering their own and others' desires (Yarnell and Neff, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that the use of compassionfocused therapy has significantly reduced the components of marital conflict. Results of this finding with the findings of Neff and Barat Wass (2013); Khalatbari, Hemmati Sabet and Mohammadi (2018); Rajabi et al (2017) are consistent. Explaining this finding, we can say that people with compassion are able to resolve their interpersonal differences by considering their own and others' desires (Yarnell and Neff, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Intimate communication is one of the most important emotional concerns in married life and also one of the important reasons for lasting marriages (Mirgain and Cordova, 2017).Over time and facing the various challenges of married life and the lack of necessary skills to improve the quality of the marital relationship, couples gradually become conflicted (Masumitabar et al, 2021).One of the treatment methods that is effective in various fields, including; Improving romantic relationships (Neff KD and Beretvas, 2013); Hope, self-esteem and mental health (Elaine Beaumont and Hollins, 2016); Intimate attitudes and reducing the desire for divorce and incompatibility and marital conflict (Dasht Bozorgi et al, 2017, Ragabi et al, 2017, Khalatbari, et al, 2018 have been successful, treatment focuses on compassion. Compassion emphasizes the important principle that images, thoughts, experiences, and soothing external and external behaviors must be internalized; In this way, the person's mind calms down in dealing with these internal and external issues (Gilbert, 2014) as it reacts to external and external issues.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the self-compassion, the more intimacy in relationships between women will increase and it will be a basis for satisfaction and positive emotions in the satisfaction of women's married life. [25] On the other hand, the findings of the covariance analysis demonstrated that compassion-based therapy has improved the scores of family functioning in the experimental group. In explaining these results, it can be said that researchers realized for a long time that soft problems and self-criticism are often rooted in family dysfunction, neglect, or lack of affection.…”
Section: Resultsmentioning
confidence: 92%
“…Compassion-focused therapy (CFT) teaches people not to avoid and suppress their painful feelings; so they can recognize their experience and be compassionate with it. This unified therapy is derived from neuroscience, social, developmental and Buddhist psychology, and many other therapeutic models of mental problems [9,10]. CFT, along with other new therapeutic approaches of the Third Wave of psychology, is designed to alleviate suffering, anxiety, and depression [3].…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of CFT implies that external thoughts, factors, images, and palliative behaviors should be internalized so that the human mind can relax in the face of these factors, in the same manner, it responds to external factors. Compassion-focused exercises emphasize relaxation, self-compassion, and mindfulness, which play a huge role in individuals' peace of mind, and alleviating stress and negative automatic thoughts [10]. There is ever-increasing empirical evidence on the effects of CFT on the whole range of psychological problems.…”
Section: Introductionmentioning
confidence: 99%